Study on Energy Saving and Optimization Controlof Metro Vehicle Based on Coasting Control - HUANG Jian; QUJianwei (机车电传动)
To reduce metro vehicle operation energy consumption, energy-saving optimal scheme based on coasting control wasstudied. According to characteristics of metro vehicle operation and energy consumption characteristics, combined with optimized trainhandling method, an energy optimization algorithm of quick search for coasting point was presented. Compared with the other twocoasting optimization approach by simulation. The results show that coasting energy-saving optimizing control method is effective toreduce train energy consumption, with not only fast processing speed, but also meeting the high-precision timing requirements, and theenergy-saving effect is 10.8% higher than the one by one coasting optimization mode, 4.5% higher than the simultaneous mode.